A classification scheme of active faults in engineering - Qingyun Zhou; Suge He; Zhenyu Zou (PLoS ONE, 2025)
Fault displacement hazard, along with ground shaking hazard and earthquake-induced geohazard, are the primary forms of disaster in major earthquakes. Buildings located on areas of strong seismic surface displacement are likely to be damaged if anti-displacement design is not carried out. Therefore, a reasonable and targeted active fault classification scheme is helpful for avoidance and anti-displacement hazard of active fault in engineering construction. However, the existing classification schemes are rough, and some have no quantitative classification basis, which makes it difficult to apply these classification schemes in actual work. Also, they did not specify whether all active faults should be avoided. In this paper, considering the physical mechanism of earthquakes, using two activity parameters of active faults, “strong earthquake recurrence period” (TRP) and “strong earthquake elapsed time ratio” (Ret), and referring to the probabilistic seismic hazard analysis method (PSHA), the maximum magnitude of potential earthquake on the fault under different exceedance probabilities (EP) is calculated, and was divided into six levels. The fault displacement hazard level under different exceedance probabilities may be different. For buildings with different importance levels, we recommend six hazard classification schemes with different exceedance probabilities. Standard buildings should avoid active faults with a fault displacement hazard level of Ⅰ ~ Ⅲ (faults that can generate earthquakes of magnitude m0 and above under a 4% exceedance probability over 100 years). Special buildings and key buildings should avoid active faults with a fault displacement hazard level of Ⅰ ~ Ⅳ (faults that can generate earthquakes of magnitude m0-0.5and above under a 1% exceedance probability over 100 years). The fault displacement hazard classification scheme given in this paper takes into account the physical mechanism of earthquake occurrence and the importance of buildings, which makes this classification scheme both scientific and practical, helps provide technical support for the design and construction of buildings. This study is still quite preliminary, and there are many issues that need further study.